The influence of type 2 diabetes mellitus on clinical manifestations of osteoarthritis - E. A. Taskina; L. I. Alekseeva; N. G. Kashevarova; E. A. Strebkova; E. P. Sharapova; N. M. Savushkina; K. M. Mikhailov; T. A. Raskina; I. B. Vinogradova; E. N. Otteva; E. V. Zonova; O. N. Anoshenkova; et al. (Современная ревматология)
Objective: to investigate in a multicenter study relationship between type 2 diabetes mellitus (DM) and clinical manifestations of osteoarthritis (OA). Material and methods. The study involved 767 patients aged 40–75 years with a confirmed diagnosis of stage I–III knee OA who had signed an informed consent form. The mean age of patients was 57.9±9.6 years, body mass index (BMI) was 30.8±6.4 kg/m2  and median duration of disease was 5 [2; 11] years. An individual record card was filled out for each patient, it contained anthropometric parameters, medical history and clinical examination data, knee pain assessment using a visual analogue scale (VAS), WOMAC, parameters of KOOS questionnaire and patient's global assessment of health. Results and discussion. DM was detected in 17.2% of cases. Patients were categorized into two groups according to the presence or absence of DM. In the presence of DM, more severe clinical manifestations of OA were noted. However, patients with DM were older, had higher BMI values, longer disease duration and were more frequently diagnosed with radiological stage III OA. After stratification by age and disease duration, individuals with DM retained worse pain scores according to VAS compared to patients without DM (median 51.5 [41.5; 70] mm versus 36 [25; 50] mm, p=0.049), total WOMAC index (1047.5 [792; 1260] mm versus 823 [536; 1145] mm; p=0.005) and its components (pain – 200 [160; 254] mm versus 155 [108; 230] mm, p=0.002; stiffness – 90 [50; 115] mm versus 60.5 [35; 100] mm, p=0.03; functional impairment – 765 [550; 918] mm versus 595 [350; 820] mm, p=0.009). Conclusion. Type 2 DM is common in patients with OA (in 17.2% of cases) and is associated with more severe clinical manifestations: greater pain intensity according to VAS and higher WOMAC scores (total index and its components).